Peningkatan Peran Kader Posyandu dalam Upaya Penurunan Angka Stunting - Enggar Liliandari; Muflih Muflih (Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting remains a public health problem that requires the involvement of various parties, including Posyandu cadres as the spearhead of health services in the community. This community service activity aims to enhance the role of Posyandu cadres in stunting prevention efforts through training and mentoring. The activity was carried out on May 18–19, 2026, in Selomartani and Purwomartani Villages, Kalasan District, involving 24 Posyandu cadre leaders. The methods used included coordination with policymakers, training on Parent Child Interaction Therapy (PCIT), responsive feeding, safe herbal use, and practice in making local food-based Supplementary Feeding (PMT). Evaluation was conducted through in-depth interviews before and after the training. The results showed an increase in cadres' understanding of their role as educators, motivators, and family companions, as well as an increase in their ability to provide education and solutions related to stunting prevention. The training and hands-on practice effectively strengthened cadres' capacity to support stunting prevention efforts in the community.